European ad-hoc consensus statement on gene replacement therapy for spinal muscular atrophy - Kirschner, Janbernd; Butoianu, Nina; Goemans, Nathalie; Haberlova, Jana; Kostera-Pruszczyk, Anna; Mercuri, Eugenio; van der Pol, W. Ludo; Quijano-Roy, Susana; Sejersen, Thomas; Tizzano, Eduardo F.; Ziegler, Andreas; Servais, Laurent; et al. (European journal of paediatric neurology, 2020)
Spinal muscular atrophy (SMA) used to be one of the most common genetic causes of infant mortality. New disease modifying treatments have changed the disease trajectories and most impressive results are seen if treatment is initiated in the presymptomatic phase of the disease. Very recently, the European Medicine Agency approved Onasemnogene abeparvovec (Zolgensma®) for the treatment of patients with SMA with up to three copies of the SMN2 gene or the clinical presentation of SMA type 1. While this broad indication provides new opportunities, it also triggers discussions on the appropriate selection of patients in the context of limited available evidence. To aid the rational use of Onasemnogene abeparvovec for the treatment of SMA, a group of European neuromuscular experts presents in this paper eleven consensus statements covering qualification, patient selection, safety considerations and long-term monitoring.
Gesehen am 11.01.2021